Method for photoelectrolyzing water by compounding non-metallic element doped fullerene with bismuth vanadate

By recombining the fullerene doped treated with non-metallic elements with BiVO4 and preparing a photoelectrocatalytic film on the FTO substrate by using hydrothermal in situ growth method, the problem of insufficient activity and stability of BiVO4 photoelectroode is solved, and high efficiency is achieved. Low-cost photoelectrolytic water electrode preparation, suitable for industrial applications.

CN119465274AActive Publication Date: 2025-02-18XI AN JIAOTONG UNIV +1

Patent Information

Application Number
CN202411665188.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-18
Estimated Expiration
2044-11-20

AI Technical Summary

Technical Problem

In the existing photoelectrolytic water technology, the redox reaction kinetics and conductivity of the bismuth vanadate (BiVO4) photoanode has poor redox reaction kinetics and conductivity, resulting in low photocurrent levels, complex catalyst preparation process and high cost, making it difficult to achieve industrial application.

Method used

Fullerene (C60) is treated by chemical vapor deposition method doping non-metallic elements (such as nitrogen, phosphorus, sulfur, boron), and recombining it with BiVO4. A photoelectro-catalytic film is prepared on an FTO substrate by hydrothermal in situ growth method to form a stable catalyst layer.

Benefits of technology

It improves the photoelectrocatalytic activity and stability of BiVO4, simplifies the preparation process, reduces costs, and realizes the efficient preparation of photoelectrolytic water electrodes, which is suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119465274A_ABST
    Figure CN119465274A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of water photoelectrolysis material preparation, and relates to a non-metallic element doped fullerene composite bismuth vanadate water photoelectrolysis method which comprises the following steps: s1, cleaning a conductive substrate; s2, the fullerene powder is subjected to non-metallic element doping treatment through a chemical vapor deposition method; s3, stirring the modified fullerene treated in the step s2, a Bi source and a V source to prepare catalyst slurry; s4, the conductive surface of a conductive base material is placed in the catalyst slurry downwards, and hydrothermal in-situ growth is carried out to prepare a photoelectrocatalysis film; and s5, naturally cooling to room temperature, taking out the conductive substrate, and heating and calcining to obtain the photoelectrolysis water electrode, according to the preparation method, fullerene is doped with different metal elements by adopting a chemical vapor deposition method, and a uniform, compact and firm catalyst film is formed on FTO (Fluorine-doped Tin Oxide) in a hydrothermal in-situ growth manner, so that a more stable and high-activity photoelectrolysis water electrode is obtained; the preparation method is simple, the cost is low, and large-scale electrode preparation can be realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of photoelectrolytic water material preparation, and relates to a method for photoelectrolytic water of a non-metallic element doped fullerene composite bismuth vanadate. Background Art

[0002] With the intensification of energy crisis and environmental problems, the realization of efficient and stable photoelectrolytic water splitting has important practical significance. Photoelectrolytic water splitting technology is a water splitting process driven by light energy. It converts solar energy or other light sources into chemical energy to decompose water molecules into valuable products such as hydrogen, oxygen, and hydrogen peroxide. This process relies on the light absorption, electron conduction and catalytic activity of photoelectrode materials. It has both energy conversion and environmental benefits and is regarded as one of the important ways to achieve a sustainable energy system. As an important research direction of solar energy conversion technology, photoelectrolytic water splitting has received widespread attention in recent years. Traditional water electrolysis technology consumes a lot of electricity, while photoelectrolytic water splitting technology utilizes solar energy through the photovoltaic effect, thereby reducing the demand for external electricity and greatly improving energy utilization efficiency.

[0003] Among many materials, bismuth vanadate (BiVO4) is widely used in photoelectrocatalysis due to its suitable band gap and good photoexcitation performance. Due to its slow redox reaction (ORR) and water oxidation reaction (WOR) kinetics, poor conductivity, and high electron-hole pair recombination rate, most reported BiVO4 photoanodes are far below the theoretically expected photocurrent level. Therefore, in the field of photoelectrocatalysis, researchers are committed to developing a variety of strategies to improve the photoelectrocatalytic activity of BiVO4. Through morphology control, doping, and composite formation of heterojunctions, its carrier mobility and conductivity can be improved, ultimately achieving the purpose of improving photoelectrocatalytic activity.

[0004] Recently, the modification method of using carbon-based materials and semiconductor metal oxides has attracted widespread attention. Specifically, carbon-based materials have excellent properties such as high specific surface area, special electronic properties, confinement effect and strong physical and chemical stability, which are conducive to further promoting photoelectrocatalysis. Although the key role of carbon-based materials as composite catalyst materials in the fields of photocatalysis, electrocatalysis and photoelectrocatalysis has been recognized, C 60 As an important part of carbon-based materials, people rarely use their electronic structure and properties to further modify them to improve their photoelectrocatalytic activity. 60 It is a carbon-based material with unique electronic properties. Due to its relatively low LUMO (lowest unoccupied molecular orbital) energy, it can be used as an excellent electron acceptor in catalytic reactions. 60The highly symmetrical cage structure makes it highly stable, but it does not provide abundant catalytic active sites in the reaction. 60 After compounding with BiVO4, the photogenerated electron transport capacity of the catalyst material can be improved to the maximum extent.

[0005] Invention CN112058275B discloses a thin film electrode alkaline photoelectrolytic water catalyst and its preparation method and application. First, two metal nanolayers of Pt and Ni are deposited in sequence on the surface of the thin film electrode, and then PtNi / Ni(OH)2 is prepared on the surface of the thin film electrode by roasting and in-situ electrochemical oxidation to obtain a target catalyst having a PtNi alloy nanolayer attached to the surface of the thin film electrode and amorphous Ni(OH)2 attached to the surface of the PtNi alloy nanolayer.

[0006] Invention CN109706478B discloses a cuprous oxide photocathode material for photoelectrolytic water splitting supported by a thin layer of titanium carbide for hydrogen reduction and a preparation method thereof. The present invention uses conductive glass or copper as a substrate to prepare cuprous oxide and supports a thin layer of titanium carbide for hydrogen reduction on its surface to synthesize a composite photoelectrode material with high photoelectrochemical performance, a cuprous oxide supported by a thin layer of titanium carbide for hydrogen reduction.

[0007] Invention CN111569896A discloses a BiVO4-Ni / Co3O4 heterogeneous synthesis method, firstly, a layer of BiOI nanoparticles is grown on a FTO substrate by electrodeposition, then an aqueous solution of vanadium acetylacetonate is dripped on the FTO surface, and bismuth vanadate (BiVO4) is generated after high-temperature calcination. Through continuous ion adsorption reaction, FTO is tilted and placed on a substrate containing Co(NO3)2·6H2O, Ni(NO3)2·6H2O, C6H 12 In a deionized water solution of N4, CH4N2O and NH4F, after hydrothermal reaction, the catalyst was taken out and washed with deionized water, annealed and then naturally cooled to room temperature to obtain the catalyst.

[0008] The invention CN109706478A discloses a cuprous oxide photocathode material for photoelectrolysis of water supported by a thin layer of titanium carbide reduced by hydrogen and a preparation method thereof. The invention uses conductive glass or copper as a substrate to prepare cuprous oxide and loads a thin layer of titanium carbide reduced by hydrogen on its surface to synthesize a composite photoelectrode material with high photoelectrochemical performance, namely, Cu2O / H:Ti3C2T x .

[0009] Invention CN105088265B discloses a cuprous oxide composite titanium dioxide nanowire array photoanode material for photoelectrolytic water splitting and a preparation method thereof. First, a hydrothermal method is used to synthesize the titanium dioxide nanowire array, and further heat treatment is performed to form anatase crystals in the titanium dioxide nanowire array. Then, in the presence of a polyamine polymer, a hydrothermal reaction is used to grow cuprous oxide on the titanium dioxide nanowire array.

[0010] The above-mentioned invention method deposits multiple metal nanolayers on the surface of the thin film electrode in sequence, and then forms a catalyst layer on the electrode surface by roasting and in-situ electrochemical oxidation. Alternatively, a cuprous oxide photocathode material is prepared on a conductive glass or copper substrate, and a thin layer of hydrogen-reduced titanium carbide is loaded on its surface to form a composite photoelectrode material with high photoelectrochemical performance. Alternatively, BiOI nanoparticles are grown on a substrate by electrodeposition, and then a BiVO4-Ni / Co3O4 heterogeneous catalyst is prepared by high-temperature calcination and continuous ion adsorption reaction. Alternatively, a titanium dioxide nanowire array is prepared by a hydrothermal method, and then cuprous oxide is grown on its surface to form a composite photoanode material for photoelectrolysis of water.

[0011] However, the preparation of these catalytic electrodes in the prior art requires a lot of pre-operations and complex process flows, which require sophisticated instruments and equipment and high-cost raw materials, and also place high demands on the operator's operating skills. In addition, most experiments do not involve more stable and more conductive carbon-based materials.

[0012] Therefore, it is crucial to seek a low-cost, simple process, and electrochemically stable and catalytic performance carbon-based catalyst and BiVO4 composite catalyst preparation method for the industrial application of photoelectrolytic water splitting. Summary of the invention

[0013] The technical solution adopted by the present invention to solve the technical problem is: a method for photoelectrolysis of water by using fullerene composite bismuth vanadate doped with non-metallic elements, comprising the following steps:

[0014] Step s1, cleaning the conductive substrate to remove impurities on the surface of the conductive substrate;

[0015] Step s2, doping the fullerene powder with non-metallic elements by chemical vapor deposition to generate modified fullerene;

[0016] Step s3, dissolving the modified fullerene treated in step s2 in solvent A; dissolving the Bi source and the V source in solvent B, and stirring to prepare a catalyst slurry;

[0017] Step s4, mixing the catalyst slurry prepared in step s3 and transferring it to a chemical reaction device, and then placing the conductive surface of the conductive substrate cleaned in step s1 downward in the chemical reaction device, and performing hydrothermal in-situ growth on it to prepare a photoelectrocatalytic film;

[0018] Step s5, after the reaction in step s4 is completed, the chemical reaction device is cooled naturally to room temperature, the conductive substrate is taken out and placed in a high-temperature heating device for heating and calcining to obtain a photoelectrolyzed water electrode;

[0019] In step s2, the non-metallic elements include: one or more of nitrogen, phosphorus, sulfur, boron, fluorine, and chlorine;

[0020] In step s3, solvent A includes: one or more of toluene, benzene, carbon tetrachloride, and isopropylbenzene; solvent B includes: one or more of ethylene glycol, ethanol, methanol, isopropyl alcohol, and deionized water.

[0021] Preferably, in step s3, the Bi source includes: one or more of bismuth nitrate pentahydrate, bismuth subcarbonate dihydrate, and bismuth sulfate, and the V source includes: one or more of ammonium metavanadate, vanadium pentoxide, and vanadium acetylacetonate.

[0022] Preferably, in step s1, the conductive substrate comprises: fluorine-doped silicon dioxide conductive glass FTO, indium tin oxide transparent conductive film glass ITO, and a stainless steel plate; in step s2, the fullerene is C 60 .

[0023] Preferably, in step s4, the chemical reaction apparatus includes: a reactor, an autoclave, a stirred reactor, a continuous flow reactor, a microreactor, an intermittent reactor, a fixed bed reactor, and a fluidized bed reactor; in step s5, the high-temperature heating device includes: a muffle furnace, a tubular furnace, a box furnace, a vacuum furnace, an atmosphere furnace, a resistance furnace, and an induction furnace.

[0024] Preferably, in step s1, the cleaning step is to use deionized water, acetone, isopropanol and ethanol to ultrasonically bathe the conductive substrate in sequence for 5-20 minutes.

[0025] Preferably, in step s2, the fullerene and the non-metallic element are fully mixed and then placed in a tube furnace and evacuated 2-5 times, and then calcined at 300-1000° C. for 1-4 hours in a N2 atmosphere.

[0026] Preferably, the hydrothermal time in step s4 is 6-18 hours, and the hydrothermal temperature is 120-200°C.

[0027] Preferably, in step s5, the temperature of the high temperature heating device is set to 350-500° C., the heating rate is 5-10° C. / min, and the calcination time is 1-4 h.

[0028] Preferably, the sizes of the conductive substrate include: 1cm*1cm, 1cm*2cm, 2cm*2cm, 2cm*3cm.

[0029] The beneficial effects of the present invention are:

[0030] The present invention uses a chemical vapor deposition method to dope fullerenes, and combines a hydrothermal in-situ growth method to evenly distribute catalyst powder on the surface of an FTO substrate to form a firm and uniform catalyst layer. After multiple photoelectrochemical tests, the catalyst does not obviously fall off and has good light transmittance. In addition, the present invention uses non-metallic element-doped fullerenes as a composite material and FTO as a raw material for electrode preparation, which has the advantages of low price, abundant output, and easy acquisition. In addition, the preparation process has low equipment requirements, is easy to operate, and has a simple preparation method, so that industrial large-scale electrode preparation can be achieved. Therefore, the photoelectrolytic water catalyst prepared by the present invention can effectively improve the photocurrent of the original BiVO4 itself, and has excellent stability. The preparation method is simple and easy to control, thereby effectively reducing the cost of photoelectrolytic water and promoting the popularization and application of this technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a scanning electron microscope morphology of an electrode sample of Example 1 of a method for photoelectrolysis of water by fullerene composite bismuth vanadate doped with a non-metallic element of the present invention;

[0032] Figure 2 This is a scanning electron microscope morphology image of the catalyst sample of Example 2 of the present invention;

[0033] Figure 3 is the XRD pattern of the catalyst sample of Example 2 of the present invention;

[0034] Figure 4 is the XPS graph of the catalyst sample of Example 2 of the present invention;

[0035] Figure 5 It is a linear sweep voltammetric curve test diagram of an example of a catalytic photoanode treated with different non-metallic elements doping according to the present invention. DETAILED DESCRIPTION

[0036] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the relevant technologies in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] The present invention aims to provide a method for photoelectrolysis of water by using non-metallic element doped fullerene composite bismuth vanadate, which has low equipment requirements, simple process and low cost in the process of electrolysis of water, further expands the selection range of composite catalysts for photoelectrolysis of water, reduces the cost of catalyst preparation, and improves the efficiency of photoelectrolysis of water.

[0038] Reference Figures 1 to 5 This embodiment provides a method for photoelectrolysis of water by using fullerene composite bismuth vanadate doped with non-metallic elements, which specifically includes the following steps:

[0039] s1: Cleaning fluorine-doped silica conductive glass (FTO) to remove impurities on the FTO surface;

[0040] s2: Fullerene (C 60 ) The powder is doped with non-metallic elements;

[0041] s3: dissolving the modified fullerene treated in s2 in toluene, dissolving the Bi source and the V source in ethylene glycol and deionized water, and stirring to prepare a catalyst slurry;

[0042] s4: The catalyst slurry prepared in s3 is mixed and transferred to a reactor with a polytetrafluoroethylene liner, and then the FTO conductive surface cleaned in s1 is placed face down in the reactor with a polytetrafluoroethylene liner, and a photoelectrocatalytic film is prepared by hydrothermal in-situ growth;

[0043] s5: After the reaction is completed, wait for the reactor to cool naturally to room temperature, take out the FTO and heat and calcine it in a muffle furnace to obtain a photoelectrolyzed water electrode.

[0044] Furthermore, in the step s1, the catalyst substrate is made of FTO with good light transmittance and conductivity, and has a size of 2cm*3cm.

[0045] Furthermore, in step s1, the cleaning step is to use deionized water, acetone, isopropanol and ethanol in sequence to ultrasonically bath the FTO for 10 minutes.

[0046] Furthermore, in step s2, the non-metallic elements are nitrogen, phosphorus, sulfur and boron, and urea, sodium hypophosphite monohydrate, sublimated sulfur and sodium borohydride are used as the nitrogen source, phosphorus source, sulfur source and boron source respectively.

[0047] Furthermore, in step s2, the fullerene and the nitrogen source are fully mixed and placed in a tube furnace and evacuated three times, and then calcined at 1000°C for 2 hours in a N2 atmosphere. The doping process of the phosphorus source, sulfur source and boron source is similar to that of the nitrogen source, and only the calcination temperature needs to be set to 800°C, 800°C and 400°C respectively.

[0048] Furthermore, in step s3, the solvent for the treated fullerene is toluene (concentration is 1 mg / 5 mL).

[0049] Furthermore, in step s3, the Bi source is bismuth nitrate pentahydrate (Bi(NO3)3·5H2O), the V source is ammonium metavanadate (NH4VO3), and the solvent is ethylene glycol and deionized water, wherein the ratio of Bi to V is 1:1.

[0050] Furthermore, in step s4, the hydrothermal time is 12 hours and the hydrothermal temperature is 180°C.

[0051] Furthermore, in step s5, the temperature of the muffle furnace is set to 400° C., the heating rate is 5° C. / min, and the calcination time is 2 h.

[0052] Example

[0053] This embodiment provides a method for photoelectrolysis of water by using fullerene composite bismuth vanadate doped with non-metallic elements, comprising the following steps:

[0054] s1: Cleaning fluorine-doped silica conductive glass (FTO) to remove impurities on the FTO surface;

[0055] s2: doping fullerene (C60) powder with non-metallic elements by chemical vapor deposition (CVD);

[0056] s3: preparing a catalyst slurry by mixing the modified fullerene treated in s2, a Bi source, a V source and a solvent;

[0057] s4: The catalyst slurry prepared in s3 is transferred to the reactor with a polytetrafluoroethylene liner, and then the FTO conductive surface after cleaning in s1 is placed face down in the reactor with a polytetrafluoroethylene liner, and a photoelectrocatalytic film is prepared by hydrothermal in-situ growth;

[0058] s5: After the reaction is completed, wait for the reactor to cool naturally to room temperature, take out the FTO and heat and calcine it in a muffle furnace to obtain a photoelectrolyzed water electrode.

[0059] Specific examples are given below to further illustrate the present invention:

[0060] Embodiment 1:

[0061] 1) FTO cleaning

[0062] Deionized water, acetone, isopropanol and ethanol were used to ultrasonically bath FTO for 10 min in sequence to remove impurities on the FTO surface so that the film could evenly cover the entire FTO surface during hydrothermal in situ growth.

[0063] 2) Preparation of catalytic thin films by hydrothermal in-situ growth

[0064] Composite catalyst thin films were grown on conductive fluorine-doped tin oxide (FTO) coated glass substrates by hydrothermal in-situ growth method. 0.485g Bi(NO3)3·5H2O and 0.117g NH4VO3 were weighed and dissolved in a mixed solvent of 20mL ethylene glycol and 10mL deionized water using a weighing balance; Bi(NO3)3·5H2O and NH4VO3 were fully mixed by magnetic stirring for 30min; the mixed solution and 5mL toluene solution were transferred to a Teflon-lined stainless steel reactor, and the pre-cleaned FTO glass substrate was placed against the wall of the Teflon lining with its conductive surface facing down. The hydrothermal time was 12h and the hydrothermal temperature was 180℃; after the reaction, the reactor was naturally cooled to room temperature.

[0065] 3) Heating and calcining

[0066] The FTO in the reaction kettle was taken out and the surface of the FTO was rinsed with deionized water. After drying at room temperature, the FTO was annealed at 400° C. for 2 hours at a heating rate of 5° C. / min in a muffle furnace to obtain a photoelectrolytic water electrode.

[0067] Embodiment 2:

[0068] 1) FTO cleaning

[0069] Deionized water, acetone, isopropanol and ethanol were used to ultrasonically bath FTO for 10 min in sequence to remove impurities on the FTO surface so that the film could evenly cover the entire FTO surface during hydrothermal in situ growth.

[0070] 2) Preparation of catalytic thin films by hydrothermal in-situ growth

[0071] The composite catalyst film was grown on a conductive fluorine-doped tin oxide (FTO) coated glass substrate by a hydrothermal in situ growth method. 0.485 g Bi(NO3)3·5H2O and 0.117 g NH4VO3 were weighed and dissolved in a mixed solvent of 20 mL ethylene glycol and 10 mL deionized water using a weighing balance; magnetic stirring was performed for 30 min to fully mix Bi(NO3)3·5H2O and NH4VO3; 1 mg C 60 Dissolve in 5 mL of toluene solution and dissolve it completely by ultrasound; transfer the two mixed solutions to a Teflon-lined stainless steel reactor, place the pre-cleaned FTO glass substrate against the wall of the Teflon liner with its conductive surface facing down, the hydrothermal time is 12 h, and the hydrothermal temperature is 180 ° C; after the reaction is completed, the reactor is naturally cooled to room temperature.

[0072] 3) Heating and calcining

[0073] The FTO in the reaction kettle was taken out and the surface of the FTO was rinsed with deionized water. After drying at room temperature, the FTO was annealed at 400° C. for 2 hours at a heating rate of 5° C. / min in a muffle furnace to obtain a photoelectrolytic water electrode.

[0074] Embodiment 3:

[0075] 1) FTO cleaning

[0076] Deionized water, acetone, isopropanol and ethanol were used to ultrasonically bath FTO for 10 min in sequence to remove impurities on the FTO surface so that the film could evenly cover the entire FTO surface during hydrothermal in situ growth.

[0077] 2) Chemical vapor deposition (CVD) of C 60 Powder is doped with B

[0078] Use a weighing balance to measure 20 mg C 60 The powder was placed in a porcelain boat for later use; 10 mg of NaBH4 was taken as the B source; after being fully mixed, it was placed in a tube furnace, and after checking the airtightness, vacuum was evacuated three times to ensure that there was no oxygen in the tube furnace; under a N2 atmosphere, it was calcined at 400°C for 2h; the treated powder was fully washed with deionized water, and dried in a forced air drying oven at 80°C, and collected for later use.

[0079] 3) Preparation of catalytic thin films by hydrothermal in-situ growth

[0080] The composite catalyst film was grown on a conductive fluorine-doped tin oxide (FTO) coated glass substrate by a hydrothermal in-situ growth method. 0.485 g Bi(NO3)3·5H2O and 0.117 g NH4VO3 were weighed and dissolved in a mixed solvent of 20 mL ethylene glycol and 10 mL deionized water using a weighing balance; the Bi(NO3)3·5H2O and NH4VO3 were fully mixed by magnetic stirring for 30 min; 1 mg of the doped BC was taken and the mixture was stirred for 30 min. 60 The powder was dissolved in 5 mL of toluene solution and completely dissolved by ultrasound. The two mixed solutions were transferred to a Teflon-lined stainless steel reactor, and the pre-cleaned FTO glass substrate was placed against the wall of the Teflon liner with its conductive surface facing down. The hydrothermal time was 12 h and the hydrothermal temperature was 180 ° C. After the reaction was completed, the reactor was naturally cooled to room temperature.

[0081] 4) Heating and calcining

[0082] The FTO in the reaction kettle was taken out and the surface of the FTO was rinsed with deionized water. After drying at room temperature, the FTO was annealed at 400° C. for 2 hours at a heating rate of 5° C. / min in a muffle furnace to obtain a photoelectrolytic water electrode.

[0083] Embodiment 4:

[0084] 1) FTO cleaning

[0085] Deionized water, acetone, isopropanol and ethanol were used to ultrasonically bath FTO for 10 min in sequence to remove impurities on the FTO surface so that the film could evenly cover the entire FTO surface during hydrothermal in situ growth.

[0086] 2) Chemical vapor deposition (CVD) of C 60 Powder N doping

[0087] Use a weighing balance to measure 20 mg C 60 The powder was placed in a porcelain boat for later use; 500 mg of urea was measured as a N source; after being fully mixed, it was placed in a tube furnace, and after checking the airtightness, vacuum was evacuated three times to ensure that there was no oxygen in the tube furnace; under a N2 atmosphere, it was calcined at 1000°C for 2h; the treated powder was fully washed with deionized water, and dried in a blast drying oven at 80°C, and collected for later use.

[0088] 3) Preparation of catalytic thin films by hydrothermal in-situ growth

[0089] The composite catalyst film was grown on a conductive fluorine-doped tin oxide (FTO) coated glass substrate by a hydrothermal in situ growth method. 0.485 g Bi(NO3)3·5H2O and 0.117 g NH4VO3 were weighed and dissolved in a mixed solvent of 20 mL ethylene glycol and 10 mL deionized water using a weighing balance; the Bi(NO3)3·5H2O and NH4VO3 were fully mixed by magnetic stirring for 30 min; 1 mg of the doped NC was taken and 60 The powder was dissolved in 5 mL of toluene solution and completely dissolved by ultrasound. The two mixed solutions were transferred to a Teflon-lined stainless steel reactor, and the pre-cleaned FTO glass substrate was placed against the wall of the Teflon liner with its conductive surface facing down. The hydrothermal time was 12 h and the hydrothermal temperature was 180 ° C. After the reaction was completed, the reactor was naturally cooled to room temperature.

[0090] 4) Heating and calcining

[0091] The FTO in the reaction kettle was taken out and the surface of the FTO was rinsed with deionized water. After drying at room temperature, the FTO was annealed at 400° C. for 2 hours at a heating rate of 5° C. / min in a muffle furnace to obtain a photoelectrolytic water electrode.

[0092] Embodiment 5:

[0093] 1) FTO cleaning

[0094] Deionized water, acetone, isopropanol and ethanol were used to ultrasonically bath FTO for 10 min in sequence to remove impurities on the FTO surface so that the film could evenly cover the entire FTO surface during hydrothermal in situ growth.

[0095] 2) Chemical vapor deposition (CVD) of C 60 Powder is doped with B

[0096] Use a weighing balance to measure 20 mg C 60 The powder is placed in a porcelain boat for later use; 500 mg of sodium hypophosphite monohydrate is measured as a P source; after being fully mixed, it is placed in a tube furnace, and after checking the airtightness, vacuum is evacuated three times to ensure that there is no oxygen in the tube furnace; under a N2 atmosphere, it is calcined at 800°C for 2h; the treated powder is thoroughly washed with deionized water, and dried in a forced air drying oven at 80°C, and collected for later use.

[0097] 3) Preparation of catalytic thin films by hydrothermal in-situ growth

[0098] The composite catalyst film was grown on a conductive fluorine-doped tin oxide (FTO) coated glass substrate by a hydrothermal in-situ growth method. 0.485 g Bi(NO3)3·5H2O and 0.117 g NH4VO3 were weighed and dissolved in a mixed solvent of 20 mL ethylene glycol and 10 mL deionized water using a weighing balance; magnetic stirring was performed for 30 min to fully mix Bi(NO3)3·5H2O and NH4VO3; 1 mg of the doped PC was taken and the mixture was stirred for 30 min. 60 The powder was dissolved in 5 mL of toluene solution and completely dissolved by ultrasound. The two mixed solutions were transferred to a Teflon-lined stainless steel reactor, and the pre-cleaned FTO glass substrate was placed against the wall of the Teflon liner with its conductive surface facing down. The hydrothermal time was 12 h and the hydrothermal temperature was 180 ° C. After the reaction was completed, the reactor was naturally cooled to room temperature.

[0099] 4) Heating and calcining

[0100] The FTO in the reaction kettle was taken out and the surface of the FTO was rinsed with deionized water. After drying at room temperature, the FTO was annealed at 400° C. for 2 hours at a heating rate of 5° C. / min in a muffle furnace to obtain a photoelectrolytic water electrode.

[0101] Embodiment 6:

[0102] 1) FTO cleaning

[0103] Deionized water, acetone, isopropanol and ethanol were used to ultrasonically bath FTO for 10 min in sequence to remove impurities on the FTO surface so that the film could evenly cover the entire FTO surface during hydrothermal in situ growth.

[0104] 2) Chemical vapor deposition (CVD) of C 60 Powder S doping

[0105] Use a weighing balance to measure 20 mg C 60The powder was placed in a porcelain boat for later use; 100 mg of sublimated sulfur was taken as the S source; after being fully mixed, it was placed in a tube furnace, and after checking the airtightness, vacuum was evacuated three times to ensure that there was no oxygen in the tube furnace; under a N2 atmosphere, it was calcined at 800°C for 2h; the treated powder was fully washed with deionized water, and dried in a blast drying oven at 80°C, and collected for later use.

[0106] 3) Preparation of catalytic thin films by hydrothermal in-situ growth

[0107] The composite catalyst film was grown on a conductive fluorine-doped tin oxide (FTO) coated glass substrate by a hydrothermal in situ growth method. 0.485 g Bi(NO3)3·5H2O and 0.117 g NH4VO3 were weighed and dissolved in a mixed solvent of 20 mL ethylene glycol and 10 mL deionized water using a weighing balance; magnetic stirring was performed for 30 min to fully mix Bi(NO3)3·5H2O and NH4VO3; 1 mg of the doped SC was taken and 60 The powder was dissolved in 5 mL of toluene solution and completely dissolved by ultrasound. The two mixed solutions were transferred to a Teflon-lined stainless steel reactor, and the pre-cleaned FTO glass substrate was placed against the wall of the Teflon liner with its conductive surface facing down. The hydrothermal time was 12 h and the hydrothermal temperature was 180 ° C. After the reaction was completed, the reactor was naturally cooled to room temperature.

[0108] 4) Heating and calcining

[0109] The FTO in the reaction kettle was taken out and the surface of the FTO was rinsed with deionized water. After drying at room temperature, the FTO was annealed at 400° C. for 2 hours at a heating rate of 5° C. / min in a muffle furnace to obtain a photoelectrolytic water electrode.

[0110] Figure 1 The scanning electron microscope morphology diagrams of Example 1 and Example 3 of the present invention are shown in FIG. X-C60 / BiVO4 photoanode thin films were prepared on FTO conductive glass substrates through hydrothermal in-situ growth and calcination treatment. Figure 1 It is clearly shown that a rice-grain-like particle structure is formed during the preparation process, and the hydrothermal in situ growth method enables the catalytic material to be more evenly distributed on the FTO conductive glass substrate. Figure 2 The transmission electron microscopy image of Example 3 shows clearly that BC 60 The / BiVO4 crystal has a relatively smooth surface, and the image has an obvious lattice spacing of 0.5105nm, which corresponds to the (1 1 2) plane of the monoclinic phase BiVO4 (PDF#83-1699). However, the lattice structure of the B-C60 / BiVO4 sample is consistent with that of BiVO4 without any change. It is difficult to confirm from the HR-TEM image that C 60 existence.

[0111] Figure 3 The X-ray diffraction (XRD) patterns of the samples of Example 1 and Example 3 of the present invention are compared. 60 With BC 60 The X-ray diffraction (XRD) spectrum shows that after the incorporation of B atoms, C 60 The diffraction peaks on the (1 1 1), (2 2 0), (3 1 1) and (22 2) planes all shift to smaller 2θ, indicating that the unit cell expansion is distorted after doping, which confirms the successful doping of element B. 60 The lattice spacing of the molecular (2 2 0) plane is 0.4918nm, which is due to the C 60 The molecular unit cell expands and distorts, resulting in an increase in the lattice spacing. However, compared with the original BiVO4 photoanode, BC 60 No obvious peak change was observed in the X-ray diffraction (XRD) pattern after the composite, which indicates that BC 60 After compounding with BiVO4, the crystal structure of BiVO4 is not changed.

[0112] Figure 4 The XPS spectra of the samples of Example 1 and Example 3 of the present invention are shown in BC 60 The characteristic XPS peaks of Bi, V and O were observed in the XPS spectra of both / BiVO4 and BiVO4; in addition, BC 60 / BiVO4 exhibits a B1s peak at a binding energy of 187 eV, indicating that BC 60 The existence of. It can be seen in the B1s spectrum that BC 60 / The B element in BiVO4 exists as B oxide and lower valence substances. Compared with BiVO4 samples, BC 60 The Bi 4f peak of the / BiVO4 photoanode shifts toward the high binding energy direction, which is attributed to the Bi (5+x)+ Based on the above results, it can be considered that the partial substitution of C with B atom 60 The C site in the 60 The change in electronegativity in turn causes the Bi site of BiVO4 to lose some electrons, which breaks the charge balance in BiVO4, further effectively attracts photogenerated electrons on the BiVO4 surface, reduces the recombination of electrons and holes in the semiconductor catalyst, and improves the overall photoelectrocatalytic performance of the composite catalyst. 60 Adding B into the 60 Activity and stability of / BiVO4 composite catalyst photoanode.

[0113] Figure 5 For the photoelectrochemical tests of different non-metallic elements doped in all embodiments of the present invention, a xenon lamp (100 mW cm -2 ) simulates the standard spectrum of the earth's surface (AM 1.5G) and measures BC in 0.5M Na2SO4 electrolyte 60 The photoelectrochemical performance of the pristine BiVO4 and untreated C 60 Composite with BiVO4 and various non-metallic elements X (X is non-metallic elements N, P and S) doped C 60 Photoelectrochemical activity of the photoanode composited with BiVO4. As shown in the figure, the photocurrent density of the original BiVO4 photoanode is relatively low (only 0.035 mA cm at 1.59 V vs. RHE). -2 ), while the unprocessed C 60 The photocurrent density of the photoanode was not significantly improved by BiVO4 because the reaction kinetics at the anode-electrolyte interface was slow and a large number of electron-hole pairs did not participate in the redox reaction on the surface. 60 The onset potential of / BiVO4 increases slightly because the unmodified C 60 The spherical structure is relatively stable, and the stable C atoms on the surface cannot serve as catalytic active sites in photoelectrocatalysis. 60 The attachment of C makes the original active sites of BiVO4 unable to be exposed, which causes the onset potential of the photoelectrocatalytic reaction to increase. 60 After non-metallic element doping, the photoelectric properties of the composite catalyst materials have changed significantly, as shown in the figure. 60 / BiVO4、SC 60 / BiVO4、BC 60 / BiVO4 catalyst photoanode has a significant increase in photocurrent density, and the photoelectrocatalytic water oxidation activity has been greatly improved. 60 / BiVO4 photoanode can reach 0.29mAcm at 1.59V vs.RHE -2 , which is 7 times that of the original BiVO4 material. The figure also shows the electrochemical impedance spectra of each sample under dark conditions and light conditions. 60 The impedance after compounding with BiVO4 is much greater than that of other samples, because the simple C 60 The heterojunction interface formed by the attachment of BiVO4 actually inhibits the transmission of electrons. However, after being doped with non-metallic elements, XC 60 The band structure changes, and the incorporation of different non-metallic element atoms leads to the C 60The electron configuration on the XC is changed, and the electronegativity of the surrounding C atoms is also changed, which has an impact on the electrons in the XC 60 and BiVO4. 60 / BiVO4、SC 60 / BiVO4、BC 60 The resistance of the NC / BiVO4 catalyst sample is similar to that of the original BiVO4 under dark conditions. 60 / BiVO4 resistance is slightly lower than that of the original BiVO4, and under light conditions, NC 60 / BiVO4、PC 60 / BiVO4、SC 60 / BiVO4、BC 60 / BiVO4 resistance is smaller than the original BiVO4, among which BC 60 / BiVO4 obtained the smallest resistance under light conditions, which indicates that B-doped C 60 After being compounded with BiVO4, the photogenerated electron transport capacity of the catalyst material can be improved to the maximum extent under visible light. Due to the presence of a large number of active sites on the surface of the composite catalyst, the current and intensity level of the anode peak increase. The compounding of carbon-based materials can enhance the adsorption capacity of ·OH on the material, which in turn improves the C 60 / BVO nanocomposite materials, thereby improving the catalytic performance of the entire photoelectrocatalyst, which is consistent with the It curve BC in the figure. 60 This is consistent with the phenomenon that / BiVO4 has the highest photocurrent.

[0114] In summary, the present invention adopts chemical vapor deposition to dope fullerene with different metal elements, and then forms a uniform, dense and firm catalyst film on FTO by hydrothermal in-situ growth, thereby obtaining a more stable and highly active photoelectrolyzed water electrode; the preparation method of the present invention is simple and low in cost, and can realize large-scale electrode preparation. Therefore, the present invention has broad application prospects in the field of photoelectrolyzed water technology.

[0115] It should be emphasized that the above are only preferred embodiments of the present invention and do not limit the present invention in any form. Any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A method for photoelectrolysis of water by using fullerene composite bismuth vanadate doped with non-metallic elements, characterized in that: The following steps are involved: Step s1, cleaning the conductive substrate to remove impurities on the surface of the conductive substrate; Step s2, doping the fullerene powder with non-metallic elements by chemical vapor deposition to generate modified fullerene; Step s3, dissolving the modified fullerene treated in step s2 in solvent A; dissolving Bi source and V source in solvent B, and stirring to prepare catalyst slurry; Step s4, mixing the catalyst slurry prepared in step s3 and transferring it to a chemical reaction device, and then placing the conductive surface of the conductive substrate cleaned in step s1 downward in the chemical reaction device, and performing hydrothermal in-situ growth to prepare a photoelectrocatalytic film; Step s5, after the reaction in step s4 is completed, the chemical reaction device is cooled naturally to room temperature, the conductive substrate is taken out and placed in a high-temperature heating device for heating and calcining to obtain a photoelectrolyzed water electrode; The non-metallic elements in step s2 include: one or more of nitrogen, phosphorus, sulfur, boron, fluorine, and chlorine; In step s3, the solvent A includes: one or more of toluene, benzene, carbon tetrachloride, and isopropylbenzene; the solvent B includes: one or more of ethylene glycol, ethanol, methanol, isopropyl alcohol, and deionized water.

2. The method for photoelectrolysis of water by using fullerene composite bismuth vanadate doped with non-metallic elements according to claim 1, characterized in that: In step s3, the Bi source includes: one or more of bismuth nitrate pentahydrate, bismuth subcarbonate dihydrate, and bismuth sulfate, and the V source includes: one or more of ammonium metavanadate, vanadium pentoxide, and vanadium acetylacetonate.

3. The method for photoelectrolysis of water by using fullerene composite bismuth vanadate doped with non-metallic elements according to claim 1, characterized in that: In the step s1, the conductive substrate includes: fluorine-doped silicon dioxide conductive glass FTO, indium tin oxide transparent conductive film glass ITO, and a stainless steel plate; In step s2, the fullerene is C 60 .

4. The method for photoelectrolysis of water by using fullerene composite bismuth vanadate doped with non-metallic elements according to claim 1, characterized in that: In step s4, the chemical reaction apparatus includes: a reactor, an autoclave, a stirred reactor, a continuous flow reactor, a microreactor, a batch reactor, a fixed bed reactor, and a fluidized bed reactor; In step s5, the high temperature heating device includes: a muffle furnace, a tube furnace, a box furnace, a vacuum furnace, an atmosphere furnace, a resistance furnace, and an induction furnace.

5. The method for photoelectrolysis of water by using fullerene composite bismuth vanadate doped with non-metallic elements according to claim 1, characterized in that: In the step s1, the cleaning step is to use deionized water, acetone, isopropanol and ethanol to ultrasonically bath the conductive substrate in sequence for 5-20 minutes.

6. The method for photoelectrolysis of water by using fullerene composite bismuth vanadate doped with non-metallic elements according to claim 1, characterized in that: In the step s2, the fullerene and the non-metallic element are fully mixed and placed in a tube furnace and evacuated 2-5 times, and then calcined at 300-1000° C. for 1-4 hours in a N2 atmosphere.

7. The method for photoelectrolysis of water by using fullerene composite bismuth vanadate doped with non-metallic elements according to claim 1, characterized in that: The hydrothermal time in step s4 is 6-18 hours, and the hydrothermal temperature is 120-200°C.

8. The method for photoelectrolysis of water by using fullerene composite bismuth vanadate doped with non-metallic elements according to claim 1, characterized in that: In the step s5, the temperature of the high temperature heating device is set to 350-500° C., the heating rate is 5-10° C. / min, and the calcination time is 1-4 hours.

9. The method for photoelectrolysis of water by using fullerene composite bismuth vanadate doped with non-metallic elements according to claim 1, characterized in that: The sizes of the conductive substrate include: 1cm*1cm, 1cm*2cm, 2cm*2cm, and 2cm*3cm.

Citation Information

Patent Citations

  • Cu₂O / TiO₂ nanowire array photoanode material for photocatalytic water splitting and its preparation method

    CN105088265B

  • Hydrogen-reduced thin-layer titanium carbide loaded cuprous oxide photo-cathode material for photoelectrolysis of water and preparation method for photo-cathode material

    CN109706478A

  • Hydrogen-reduced thin-layer titanium carbide-supported cuprous oxide photocathode for photoelectrochemical water splitting and its preparation method

    CN109706478B

  • Thin-film electrode alkaline photoelectrochemical water splitting catalyst, its preparation method and application

    CN112058275B

  • Method for preparing fullerene self-assembled nanometer bismuth vanadate photocatalyst

    CN102489292A

Cited By

  • Preparation method and application of high-performance LaCo-LDH / NiPt / BVO photoelectrode film

    CN119980293A

  • Preparation and application method of nickel-based electrode for hydrogen evolution by electrolyzing water

    CN119980319A